Some herding, record keeping and treatment methods used in Alaskan reindeer herds - Dieterich, Robert A. (Rangifer, 1986)
Approximately 20000 reindeer (Rangifer tarandus) in Alaska are gathered once or twice yearly to facilitate identification, serologic sampling, treatment and antler removal. Various air and land craft are used to bring the animals into a corral system from which they can be herded into a padded, pneumatically operated, squeeze apparatus. Ear tags are applied or read if already in place and ears are notched. A portable, computerized rapid data retrieval system is used to record reproductive success, vaccination and treatment status and other miscellaneous information. Ivermectin is being administered in the early winter months to treat reindeer in many herds for warbles, nasal bots and internal parasites. A killed, homologous Brucella suis type 4 vaccine is being used in two large (3500) herds. Efforts are being made to incorporate other innovative methods to improve herding and corralling methods.